The rise and fall of citizen Black - Small, Martin; BBC worldwide (North Sydney, N.S.W. : BBC Worldwide, 2004)
Jeff Randall investigates the rise and fall of the Canadian born media tycoon Conrad Black
Camera: Neil Higginson ; sound, George Kidson
DVD format
Keywords: Black, Conrad; Businessmen -- Canada; Capitalists and financiers -- Canada